THE EFFECT OF PLANT GROWTH REGULATOR TRIACONTANOL TO THE GROWTH OF CACAO SEEDLINGS (Theobroma cacao L.) - Sitinjak, Rama Riana; Pandiangan, Dingse (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
The aim of this study was to evaluate the effect ofÂ plant growth regulator triacontanol to the growth of cacao seedings (Theobroma cacao L.). A completely randomized design was applied using non-factorial pattern on the treatment triacontanol growing regulator substance to level: 0.0 ml/L, 0.1 ml/L, 0.5 ml/L, 1.0 ml/L and 2.0 ml/L replicated 5 times. The result shows that the given of tria-contanol significantly affected the growth of cacao seedings at the age of 14 weeks. The best tria-contanol concentration was 1.0 ml/L, which was effectively able to increase the growth of cacao seedlings; high seedlings, number of leaves, lenght of leaves, and diameter of stems respectively reached 26.21%; 3.70%; 42.28%; and 10.42% higher than the control. Plant growth regulator triacontanol was efective to increase the growth of cacao seedlings.Â Keywords: triacontanol, seedling, Theobroma cacao L.